Description of a new species of Betrichia Mosely 1939 from Brazil and edescription of the type-species (Trichoptera: Hydroptilidae: Leucotrichiinae) - Souza, Wagner Rafael M. De; Santos, Allan Paulo Moreira; Takiya, Daniela Maeda (Zootaxa, 2016)
Betrichia Mosely 1939 was erected to include a single species, B. zilbra Mosely 1939 from Brazil. The genus has a complicated taxonomy mainly because of the lack of diagnostic characteristics in the original description. Marshall (1979) stated that some features of the antennae, wing venation, and male genitalia are presumably diagnostic, but it remained without a precise diagnosis. Currently, Betrichia comprises 11 Neotropical species (Flint et al. 1999; Oláh & Johanson 2011; Thomson 2012; Oláh & Flint 2012), six of which have been recorded from Brazil (Santos et al. 2015): B. alibrachia Thomson 2012 (Rio de Janeiro State), B. hamulifera Flint 1983 (Pernambuco, São Paulo, and Santa Catarina states), B. kagyla Oláh & Flint 2012 (Amazonas State), B. longistyla Flint 1983 (Santa Catarina State), B. varratlana Oláh & Flint 2012 (Rondônia State), and B. zilbra Mosely 1939 (Santa Catarina State). Herein, we describe and illustrate a new species of the genus and redescribe the type-species of the genus based on topotypical specimens. We also provide new distributional records for Betrichia zilbra, reported here for the first time from Argentina (Misiones) and Bahia and Sergipe states (Brazil), and for Betrichia bispinosa Flint 1974, representing the first record of this species in Brazil (Amapá and Pará states).